2014
DOI: 10.1109/tns.2014.2335208
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-Gamma Pulse Shape Discrimination Using Organic Scintillators With Silicon Photomultiplier Readout

Abstract: Neutron/Gamma pulse shape discrimination (PSD) was measured using stilbene and EJ-299-34 plastic scintillators with readout by silicon photomultipliers (SiPMs). The SiPM pulses were digitized and processed for energy and pulse shape information using a digital technique performing numerical weighted integrations on each pulse. A genetic algorithm (GA) was developed to optimize the weighting vectors used for the pulse shape discrimination. Efficient PSD was obtained down to an electron-equivalent energy of 127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…When coupled to a scintillating medium, these devices have been used in a variety of radiation detection and spectroscopy applications including dosimetry [3,4], medical imaging [5][6][7][8], high-energy physics [9][10][11], and homeland security [12][13][14]. Additionally, organic crystals with pulse shape discrimination (PSD) capabilities coupled to SiPMs have been shown to be capable of fast-neutron detection [15][16][17]. Previous approaches used complex PSD algorithms and exhibited poorer PSD performance with SiPMs when compared to PMTs.…”
Section: Introductionmentioning
confidence: 99%
“…When coupled to a scintillating medium, these devices have been used in a variety of radiation detection and spectroscopy applications including dosimetry [3,4], medical imaging [5][6][7][8], high-energy physics [9][10][11], and homeland security [12][13][14]. Additionally, organic crystals with pulse shape discrimination (PSD) capabilities coupled to SiPMs have been shown to be capable of fast-neutron detection [15][16][17]. Previous approaches used complex PSD algorithms and exhibited poorer PSD performance with SiPMs when compared to PMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Dark pulses arise from thermally generated electrons initiating avalanches in high-field regions, while after-pulsing is triggered by the release of trapped charges within the silicon crystal, leading to a secondary avalanche within the same micro-cell. The occurrence of these phenomena is influenced by pixel recovery times, as discussed in [8], [9]. Another challenge encountered in SiPMs arises when covering extensive areas, leading to high capacitance, and consequently, the need for pre-amplification stages.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it must be recognized that the conversion of light into charge in a SiPM does not follow the same principles as in a PMT. Several authors have demonstrated the possibility to perform neutron/gamma-ray using millimeter scale scintillators coupled to single SiPMs, obtaining good results [8], [16], [17]. However, when large area SiPMs (array of single SiPMs) are coupled to medium-sized scintillators, achieve n/γ discrimination performance comparable with the one obtained with the PMTs is still a significant challenge, as reported in [18]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, SiPMs have been used in a variety of fields, such as particle and nuclear physics, medical imaging and homeland security [1]- [3]. It has been shown that SiPMs, coupled to specifically engineered scintillators with sensitivity to both fast and slow neutrons, represent a viable solution for the discrimination of light pulses originated by gamma rays against neutrons [4]. The enabling feature of this class of scintillators is the different light emission time in response to interactions of neutrons or gamma rays.…”
Section: Introductionmentioning
confidence: 99%